Microbial community structure and diversity of endophytic and rhizosphere of Cypripedium species in Changbai Mountains - Yuze Shan; Xi Lu; Shizhuo Wang; Hao Cong; Qi Wang; Jiahui Yu; Yiting Xiao; Nan Jiang; Lifei Chen; Yunwei Zhou (Ornamental Plant Research)
Cypripedium is an important ornamental plant. However, it is facing increasing endangerment due to habitat destruction and illegal collection. Therefore, the conservation of Cypripedium is becoming increasingly important. Fungi are involved in the entire life cycle of Cypripedium plants. A growing number of experiments have shown that the mycorrhizal communities of Cypripedium have also diversified under different growth environments, and most of such studies have explored the relationship between endophytic fungi in the root and the environment. Fourteen fungal and 34 bacterial phyla were detected in roots and rhizosphere samples. Ascomycota, Basidiomycota, Mortierellomycota, and Chytridiomycota content were higher in endophytic fungi. Cadophora was detected in four species of Cypripedium and was dominant among the endophytic fungi, the content was up to 80.81% ± 9.84%. Cadophora had the function of altering the structure of endophytic fungi of Cypripedium. Endophytic bacteria were mainly detected with high abundance of Pseudomonadaceae, Rhizobiaceae, Streptomycetaceae, Burkholderiaceae, and Rickettsiacea, which were endophytic in different Cypripedium plants. The diversity of rhizosphere fungi was higher than the diversity of endophytic fungi, C. shanxiense had the highest fungal community richness within four Cypripedium species and predicted that endophytic bacteria had reductive citrate cycle, 3-hydroxypropionate bicycle, and other functions. These endophytes comprise unique Cypripedium plants' microbial community structure in Changbai Mountain (China), providing a direction for further protecting wild Cypripedium resources. Understanding the structural characteristics of the endophytic fungal community of Cypripedium under the environment of Changbai Mountain provides a direction for further conservation of Cypripedium in Changbai Mountain, and exploring the functions of different types of fungi during the growth process of Cypripedium provides a theoretical basis for the subsequent exploration of the species of Cypripedium endophytes in different habitats as well as the effects on the root and soil endophytes of Cypripedium plants.